2020
DOI: 10.1080/17483107.2020.1849433
|View full text |Cite
|
Sign up to set email alerts
|

Can google glass™ technology improve freezing of gait in parkinsonism? A pilot study

Abstract: Purpose: Freezing of gait (FOG) is a disabling phenomenon defined by the periodic absence or reduction of forward progression of the feet despite the intention to walk. We sought to understand whether Google Glass (GG), a lightweight wearable device that provides simultaneous visual-auditory cues, might improve FOG in parkinsonism. Methods: Patients with parkinsonism and FOG utilized GG custom-made auditory-visual cue applications: "Walk With Me" and "Unfreeze Me" in a single session intervention. We recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
1
8
0
1
Order By: Relevance
“…Our initial usability data, 18 and others, 49 support the feasibility of using head-mounted AR devices in PwPD. Individuals with PD typically experience no motion sickness, find the device relatively comfortable, 49 and report positive usability scores following single bouts of activity. 18 However, preliminary efficacy of head-mounted AR devices in treating PD symptoms has been mixed.…”
Section: Discussionsupporting
confidence: 68%
“…Our initial usability data, 18 and others, 49 support the feasibility of using head-mounted AR devices in PwPD. Individuals with PD typically experience no motion sickness, find the device relatively comfortable, 49 and report positive usability scores following single bouts of activity. 18 However, preliminary efficacy of head-mounted AR devices in treating PD symptoms has been mixed.…”
Section: Discussionsupporting
confidence: 68%
“…Figure 4 shows VR tremor test results that matched with UPDRS-III tremor sub-scores in a 67-year-old right-handed female patient. Since this is the first study using VR to measure motor dysfunction in a patient population undergoing [ 123 I]FP-CIT SPECT/CT brain imaging, there is potential for further improving VR performance with test optimization and implementation of more advanced technologies such as augmented reality, a smaller headset, and glove controllers that can track the motion of the upper extremity digits [25].…”
Section: Discussionmentioning
confidence: 99%
“…Mobile smart glass technology like google glass that use visual and auditory cueing have shown to benefit FOG. Study showed that improvement of average 25 feet straight walk by 0.32 seconds and through doorway by 0.59 seconds [53].…”
Section: Newer Techniques To Improve Fog In Pdmentioning
confidence: 93%